The Influence of Promotions and Shopping Lifestyle on Impulsive Purchases through Positive Emotions as an Intervening Variable in the Balyan Shop Online Store - Tri Widiyanti; Endang Sulistya Rini; Syafrizal Helmi Situmorang (Budapest International Research and Critics University, 2022)
Along with the development of an increasingly modern business, marketers are required to have an effective strategy to create market share for consumers. Balyan Shop is an online store located in East Aceh and is engaged in retail, especially fashion. This study aims to determine the effect of promotion and lifestyle on impulse purchases through positive emotions as an intervening variable at the online store Balyan Shop. This research is a quantitative study with an associative approach, namely to determine the relationship between two or more variables. The types of data used in this study are primary data and secondary data. The population represented in this study represents all customers of the online store Balyan Shop, the exact number of whom is unknown.